Upgrading Students’ Interest melalui Model Pembelajaran Color-Coded Co-op Cards (CoCoCa) di Madrasah Ibtidaiyah - Muhammad Mushfi El Iq Bali; Mahfud Dhofir Jailani; Moh. Nadir Romaodhoni; Ratnawati Ratnawati (MANAZHIM, 2021)
Low student interest in learning affects student learning outcomes. Thus, stimulation is needed to increase student interest in learning so that it can improve student learning outcomes. This study aims to determine the application of the Color-Coded Co-op Cards (CoCoCa) learning model in increasing students' interest in learning towards Islamic Education in MI Tarbiyatul Islamiyah Sumberkerang Gending Probolinggo and its supporting and inhibiting factors. This study uses a qualitative research approach. The type used in this research is a case study. The results of the study are based on data exposure and interview results, the Color-Coded Co-op Cards (CoCoCa) learning model is very suitable to be applied in MI Tarbiyatul Islamiyah Sumberkerang Gending Probolinggo the Color-Coded Co-op Cards (CoCoCa) cooperative learning model is able to create an atmosphere and learning conditions that are pleasant and not saturating. This is different from the findings in the observation results, when the teacher uses the lecture method, the majority of students feel boredom so that students passively participate in learning and even fall asleep in the classroom. However, when the teacher applies the Color-Coded Co-op Cards (CoCoCa) learning model, it is known that the percentage of student interest in learning increases by up to 85% to be more active in learning compared to other learning model.